Do greenhouse experiments predict willow responses to long term flooding events in the field? - Cerrillo, Teresa (2013)
Flooding tolerance should be included as a trait in breeding programs in forested areas where extreme flooding events lasting several months can occur. In this context, it is difficult to carry out controlled, long-term flooding experiments with big trees due to the large number of specimens to screen. The hypothesis in this work was that a relatively short-term flooding experiment in a greenhouse would be useful to select clones capable of enduring long term flooding events in the field. The survival of 4 willow clones in a long term, 12 years field trial that was subjected twice to long term flooding events, was compared with the survival, growth and gas exchange of those same clones subjected to flooding in the greenhouse for three months. There were differences in flooding survival in the field: clone AN4 showed a 100 % survival, followed by clone 395 (43 %), clone 131-27 (18 %) and clone 13-44 (14 %). In the greenhouse, all plants survived and only flooded plants of clone 13-44 experienced a statistically significant growth and stomatal conductance reduction. The flood tolerance ranking in the field and in the greenhouse only partially overlapped; the worst clone in the field could be identified in the short-term greenhouse experiment, though the best one could not. It was not possible to identify clones with tolerance to long-term flooding episodes in the field. Nevertheless, the greenhouse results were useful to identify clones showing flooding sensitivity and tolerance to short term flooding episodes.